Feline Calicivirus: A comprehensive review - Hardi Marif; Hana raoof; kwestan Ali; saman muhamad; Basim Ali; Rizgar Sulaiman; othman nasrullah (Basrah Journal of Veterinary Research)
A highly mutated RNA virus known as feline Kalisi virus (FCV) is commonly found in domestic cats. However, its potential for transmission to humans is minimal. FCV has significant genetic and antigenic diversity in cat populations. Severe acute systemic FCV infection (VS-FCV) manifests itself as lingual ulcers for upper respiratory tract diseases, gingivitis, alopecia, skin, mouth, ear problems, and claudication syndrome. Other symptoms include necrosis of the pancreas, liver, and spleen, bronchointerstitial pneumonia, and subcutaneous edema that contribute to the high mortality rate of infected cats. The diagnosis of FC virus is carried out using two techniques: reverse transcription-polymerase chain reaction (RT-PCR) and virus isolation. The frequency of antibodies is usually high in cat populations due to vaccination and symptomatic diseases. Therefore, the presence of certain antibodies does not always indicate the presence of a prolonged infection. The mainstay of FCV treatment is supportive care, although there are no authorized antiviral drugs specifically designed for the virus. However, drugs such as misuripine and nitazoxanide have proven their antiviral effectiveness in the laboratory. The types of vaccines available include inactivated and modified vaccines. Vaccination is necessary for the prevention of FCV virus. Preventing the spread of FCV requires proper hygiene and effective disinfection, especially in versatile environments.